Improving students’ korfball skills with in-depth content knowledge - DERVENT, FATİH; GÜLER, MELİKE LALE (My University, 2022)
© 2022 SHAPE America.In this article, we present in-depth content knowledge required for preservice and practicing physical education teachers to teach korfball. We begin by describing knowledge of game rules, safety, etiquette, techniques, and tactics of korfball, which refers to common content knowledge (CCK) and continue with defining knowledge of student errors, instructional tasks, and representations. This refers to specialized content knowledge (SCK) that is essential for teachers to deliver meaningful learning experiences to students in physical education lessons. The article provides preservice and practicing physical education teachers with educationally rich examples to improve their teaching practices, thus promotes students’ lifelong engagement in korfball.
Keywords: Tıp; Dahili Tıp Bilimleri; Fiziksel Tıp ve Rehabilitasyon; Cerrahi Tıp Bilimleri; Ortopedi ve Travmatoloji; Sosyal ve Beşeri Bilimler; Sosyoloji; Eğitim; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Physical Medicine and Rehabilitation; Surgery Medicine Sciences; Orthopedics and Traumatology; Social Sciences and Humanities; Sociology; Education; Health Sciences; Klinik Tıp (MED); Sosyal Bilimler (SOC); Klinik Tıp; Sosyal Bilimler Genel; REHABİLİTASYON; ORTOPEDİ; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Clinical Medicine (MED); Social Sciences (SOC); CLINICAL MEDICINE; SOCIAL SCIENCES, GENERAL; REHABILITATION; ORTHOPEDICS; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Ortopedi ve Spor Hekimliği; Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Social Sciences & Humanities; Orthopedics and Sports Medicine; Physical Therapy, Sports Therapy and Rehabilitation